THE CONFLUENCE OF SUPPORT AND OUTLOOK: EVALUATING RESILIENCE FACTORS AMONG CHANDIGARH'S GOVERNMENT SCHOOL ADOLESCENTS. - Jaswant Singh; Professor Seema Vinayak (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This study examined the perceptions of social support, optimism, and resilience among adolescents from government schools in Chandigarh. A sample of 200 adolescents (102 male and 98 female) was assessed using the LOT-R by Scheier & Carver, 1994, CYRM-R by Jefferies et al., 2018, and the MSPSS by Zimet et al., 1988. The Pearson Correlation and Multiple Regression Analysis was performed using SPSS (version 26). The findings revealed a significant positive correlation between the variables and their subscales. Also perceived social support and optimism both predicted resilience significantly. These results underscore the potential benefits of interventions aimed at enhancing optimism and social support networks to foster resilience in this population. The implications of these findings for psychological well-being and educational practices are discussed.